Inhalation of Essential Oil from Mentha piperita Ameliorates PM10-Exposed Asthma by Targeting IL-6/JAK2/STAT3 Pathway Based on a Network Pharmacological Analysis - Mi Hye Kim; Sang Jun Park; Woong Mo Yang (MDPI AG, 2020)
Fine particulate matter (PM) exposure exhibits a crucial risk factor to exacerbate airway epithelial remodeling, fibrosis, and pulmonary destruction in asthma. Based on the use of essential oils from aromatic plants on pain relief and anti-inflammatory properties, we investigated the inhibitory effects of essential oil derived from the Mentha species (MEO) against asthma exposed to PM10. The MEO (0.1 v/v %) was aerosolized by a nebulizer to ovalbumin and PM10-induced asthmatic mice. Histological changes were confirmed in the lung tissues. To define the mode of action of the MEO on asthma, a protein-protein interaction network was constructed using menthol and menthone as the major components of the MEO. Cytokine expression and the JAK2/STAT3 signaling pathway were analyzed in lung epithelial A549 cells co-treated with MEO and PM10. Inhalation of MEO by nebulization inhibited respiratory epithelium hyperplasia, collagen deposition, and goblet cell activation in asthmatic mice. Through a network pharmacological analysis, cytokine-cytokine receptor interaction and JAK/STAT was expected to be underlying mechanisms of MEO on asthma. Treatment with MEO significantly reduced the IL-6 levels with a decrease in pro-inflammatory and T helper 2-specific cytokines. PM10-induced phosphorylation of JAK2 and STAT3 was significantly decreased by MEO. Collectively, MEO may have an inhibitory effect on asthma under the condition of PM10 exposure through the IL-6/JAK2/STAT3 signaling pathway.